2018
DOI: 10.1021/acs.orglett.8b01363
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Lactonization of Unactivated Aryl C–H Bonds with CO2: Experimental and Computational Investigation

Abstract: The first catalytic lactonization of unactivated aryl C-H bonds with CO to afford important phthalides is reported. Notably, this method features high selectivity, excellent functional group tolerance, smooth scalability, and facile product diversification. DFT calculations reveal that a novel insertion of two CO into the O-Pd bond of a palladacycle might be the key step, providing great potential and a different perspective for carbonylation with CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 91 publications
1
22
0
Order By: Relevance
“…Mechanistic investigations suggested that the palladacycle might be an active intermediate, which further reacted with CO 2 to generate the desired product. In another work, with benzylic alcohol as a directing group, the authors achieved [Pd(tfa) 2 ]‐catalyzed lactonization of unactivated aryl C−H bonds with CO 2 to afford phthalides (Scheme b). Remarkably, DFT calculations indicated that lactonization might involve insertion of two CO 2 into the O−Pd bond of the palladacycle, which is interesting and novel compared with previous reports.…”
Section: Carboxylation Of C(sp2)−h Bonds With Co2mentioning
confidence: 99%
“…Mechanistic investigations suggested that the palladacycle might be an active intermediate, which further reacted with CO 2 to generate the desired product. In another work, with benzylic alcohol as a directing group, the authors achieved [Pd(tfa) 2 ]‐catalyzed lactonization of unactivated aryl C−H bonds with CO 2 to afford phthalides (Scheme b). Remarkably, DFT calculations indicated that lactonization might involve insertion of two CO 2 into the O−Pd bond of the palladacycle, which is interesting and novel compared with previous reports.…”
Section: Carboxylation Of C(sp2)−h Bonds With Co2mentioning
confidence: 99%
“…Recently, Yu and coworkers reported a lactonization reaction of unactivated aryl C−H bond with CO 2 . They proposed a mechanism based on the DFT calculation . Referring to their work and our preliminary mechanistic studies, a possible mechanism is proposed for this present catalytic reaction (Scheme ).…”
Section: Methodsmentioning
confidence: 80%
“…Attempts to tease the intermediates out by mass spectrometry led to the observation of an interesting adduct involving two carbon dioxides, potentially implicating a unique nine-membered palladacycle (Scheme 6a) (a similar nine-membered metallacycle was recently supported computationally in another work). 42 Notably, under the optimized conditions, no α or β C-H activation of methyl groups (from a five-membered or six-membered palladacycle respectively) could be achieved, suggesting that if a tran-…”
Section: Mechanistic Questionsmentioning
confidence: 99%